Content curation articles. Categories and examples - Guallar, Javier (Anuario ThinkEPI, 2017)
A proposal of indicators for the analysis of articles based on content curation is presented. Two fundamental parameters are considered: curation and content, and for each, several indicators are proposed with types of articles and examples.
Keywords: Content curation; Articles; Blogs; Digital publications; Content; Sense making.